Behaviour of Some Pyridine Ligands Coordinated to Co(III) in Alkaline Solution - Mobinikhaledi, A.; Forughifar, N.; Dastgani, S. (Asian Journal of Chemistry, 2012)
[Co(NH3)5L](ClO4)3 (L = pyridine, 2-, 3-, and 4-methylpyridine) were synthesized by reaction of [(NH3)5Co(DMSO)(ClO4)3] and an appropriate ligand in DMSO solution at 80-85 ºC. The behaviour of these complexes in alkaline solution indicated that there is no evidence for the possibility of covalent hydration or pseudobase formation. However, under alkaline solution (D2O/OD–) deuterium exchange is the only possibility which can occur on the ortho positions of pyridine ligands coordinated to Co(III).